A few words about the mediatization of memory, it is, how "Polityka" and "Tygodnik Powszechny" have built narration on Polish-German reconciliation in 1965-1989/90 - Dec-Pustelnik, Sylwia (Political Preferences, 2017)
Mediatization of politics, including historical politics which takes a crucial part in the process of creating collective memory, is a fact. Media - as a carrier of memory - are used to circulate the images of the past and the present and give meaning to them. The objective of this article was an attempt to analyze Polish media discourse between 1965 and 1989/90 with reference to the phenomenon of creating memory about Polish-German reconciliation. In what way, taking into consideration the role of press and media in creating memory, was the memory about the most significant in the discussion about Polish-German reconciliation events (Letter of Reconciliation of the Polish Bishops to the German Bishops, kneeling of Willy Brandt in front of the monument commemorating 500 thousand Jewish people murdered by Nazis) created, presented, in what way was it commemorated in "Tygodnik Powszechny" and "Polityka" between 1965-1989/90. The following paper attempts to describe the changing media discourse (its elements and qualities) which was the basis for building the image of Polish-German reconciliation emerging from the source material. Key words: media discourse, mediatization, memory studies, Poland, German, reconciliation